2020
DOI: 10.5195/ijt.2020.6319
|View full text |Cite
|
Sign up to set email alerts
|

User Preferences for Privacy Protection Methods in Mobile Health Apps: A Mixed-Methods Study

Abstract: Background: Mobile health (mHealth) apps have the potential to facilitate convenient health care delivery and self-management of health. However, many users have concerns about their privacy when they use mHealth apps. Different apps provide different solutions for protecting users’ privacy. Objective: The purpose of this study was to determine user preferences among the several privacy protection methods used in current mHealth apps and the reasons behind their preferences. Methods: Five privacy protection me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Users also highlighted that it would be beneficial to selectively grant permissions, for example, granting periods of access to shared data as opposed to unrestricted and the ability to remove permissions to certain parties if and when deemed appropriate. Related to this theme is Hiding Information , referenced by one publication [ 53 ], to avoid accidental disclosure to bystanders who might observe app use—relating to the earlier Fear of Misuse through Theft or Accidental Disclosure theme. It is suggested that parts of apps could be hidden quickly and flexibly so that shared data cannot be seen by third parties.…”
Section: Resultsmentioning
confidence: 99%
“…Users also highlighted that it would be beneficial to selectively grant permissions, for example, granting periods of access to shared data as opposed to unrestricted and the ability to remove permissions to certain parties if and when deemed appropriate. Related to this theme is Hiding Information , referenced by one publication [ 53 ], to avoid accidental disclosure to bystanders who might observe app use—relating to the earlier Fear of Misuse through Theft or Accidental Disclosure theme. It is suggested that parts of apps could be hidden quickly and flexibly so that shared data cannot be seen by third parties.…”
Section: Resultsmentioning
confidence: 99%
“…Zhou and Parmanto used a mixed methods design to study what users of mobile health apps preferred in terms of privacy protections when using mHealth apps that Findings from the 2021 Yearbook Section on Health Information Management contained sensitive health information [13]. Even though the users may have decided themselves to use the apps, they wanted methods to protect their privacy, not just of the information contained in the apps, but even the fact that they were using the app.…”
Section: Privacy and Securitymentioning
confidence: 99%
“…Additionally, people may refuse to use mHealth apps because of concerns about health data security and privacy [49,50]. Furthermore, concerns about privacy protection are exacerbated by people's sense of shame about using mental health services [51][52][53]. However, the trust between app developers and users may be damaged by the lack of clarity of privacy policies, which results in the loss of potential long-term users [54].…”
Section: Principal Findingsmentioning
confidence: 99%